2016
DOI: 10.1007/s11357-016-9936-8
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated vulval integrity is an important marker of nematode healthspan

Abstract: Improving healthspan, defined as the period where organisms live without frailty and/or disease, is a major goal of biomedical research. While healthspan measures in people are relatively easy to identify, developing robust markers of healthspan in model organisms has proven challenging. Studies using the nematode Caenorhabditis elegans have provided vital information on the basic mechanisms of aging; however, worm health is difficult to define, and the impact of interventions that increase lifespan on worm he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…The extrusion through vulva phenotype, observed in ∼30% of famk-1Δ worms (Figs. 1 D and S1 B), indicative of loss of vulval integrity (Reinhart et al, 2000;Leiser et al, 2011Leiser et al, , 2016, was also rescued by psth-1-driven FAMK-1 (0/25 worms analyzed exhibited this phenotype), potentially due to the sth-1 promoter being active in specific vulval cells (Fig. 6 B).…”
Section: Clec-233 Phosphorylation By Famk-1 Contributes To the Embryomentioning
confidence: 81%
“…The extrusion through vulva phenotype, observed in ∼30% of famk-1Δ worms (Figs. 1 D and S1 B), indicative of loss of vulval integrity (Reinhart et al, 2000;Leiser et al, 2011Leiser et al, , 2016, was also rescued by psth-1-driven FAMK-1 (0/25 worms analyzed exhibited this phenotype), potentially due to the sth-1 promoter being active in specific vulval cells (Fig. 6 B).…”
Section: Clec-233 Phosphorylation By Famk-1 Contributes To the Embryomentioning
confidence: 81%
“…6 C). The extrusion through vulva phenotype, indicative of loss of vulval integrity (Reinhart et al 2000;Leiser et al 2011;Leiser et al 2016), was also rescued by psth-1-driven FAMK-1 (not shown), potentially due to the sth-1 promoter being active in specific vulval cells ( Fig. 6 A).…”
Section: Famk-1∆mentioning
confidence: 88%
“…However, no perfect consensus can be reached on the concept of being 'healthy', as it is an umbrella term covering many facets of quality of life. Several groups have used different physiological parameters to describe health in C. elegans, such as oxidative and heat stress resistance, pharyngeal pumping and autofluorescence [6], vulval integrity [27], intestinal atrophy [28], muscle integrity and yolk production [10]. We here selected daily, stimulated peak activity over daily, stimulated average/median activity as a readout for overall health, as peak values were most robust and less prone to day-to-day activity variations (Fig 5 and S2 Table).…”
Section: Discussionmentioning
confidence: 99%